Persisting vitamin D deficiency in the Asian adolescent. Issue 8 (August 1984) - O'Hare, A E; Uttley, W S; Belton, N R; Westwood, A; Levin, S D; Anderson, F
Abstract : A study of 221 children admitted to hospital in the course of a year allowed establishment of a reference range for plasma 25-hydroxyvitamin D. None of these children had evidence of biochemical rickets. Most Asian children, however, were vitamin D deficient in comparison, and this deficiency was most noticeable in girls aged 13 to 15 years: biochemical rickets occurred in six per cent of these adolescent Asians. If vitamin D requirements are not met during the physiological growth spurt, permanent pelvic deformity may result. Vitamin D deficiency persisting into pregnancy will adversely affect the infant, producing an increased risk of hypocalcaemic fits, dental enamel hypoplasia, infantile rickets, and reduced postnatal growth. Our data support the need for vitamin D supplementation, and we suggest that annual oral vitamin D supplements in the autumn would alleviate the problem.